Two-Year Toxicity and Efficacy of Carbon Ion Radiotherapy in the Treatment of Localized Prostate Cancer: A Single-Centered Study - Li, Ping; Hong, Zhengshan; Li, Yongqiang; Fu, Shen; Zhang, Qing (Frontiers in Oncology, 2022)
Background We aimed at determining the safety and feasibility of spot-scanning carbon ion radiotherapy (CIRT) for patients with localized prostate cancer. Methods We enrolled 118 patients with localized prostate cancer who underwent treatment with spot-scanning CIRT at the Shanghai Proton and Heavy Ion Center (SPHIC) from January 2016 to December 2020. The dose was gradually increased from relative biological effectiveness (RBE)-weighted dose (DRBE) = 59.2–65.6 Gy in 16 fractions. The primary endpoint was the occurrence of acute and late toxicities, while the secondary endpoints were biochemical relapse-free survival (bRFS), distant metastasis-free survival (DMFS), prostate cancer-specific survival (PCSS), and overall survival (OS). Results The median follow-up time was 30.2 months (4.8–62.7 months). Acute grade 1 and 2 genitourinary (GU) toxicities were 15.3% and 18.6%, while acute grade 1 and 2 gastrointestinal (GI) toxicities were 2.5% and 0%, respectively. Late grade 1 and 2 GU toxicities were 4.2% and 1.7%, respectively. No late GI toxicity was observed. Moreover, there were no cases of severe acute or late toxicity (≥ grade 3). No significant association were observed between the factors and the acute GU toxicities, except for clinical target volume (CTV) (p = 0.031) on multivariate analysis. The 2-year bRFS, DMFS, PCSS, and OS were 100%, 100%, 100%, and 98.8%, respectively. Conclusion The 2-year outcomes were encouraging, providing additional and useful information on the feasibility and safety of spot-scanning CIRT for treating prostate cancer. Thus, we recommend long-term follow-up and prospective multicentered studies to reinforce the role of CIRT in the management of localized prostate cancer.